Identifikasi Hama Penggerek Batang dan Deskripsi Kerusakan pada Tanaman Melina (Gmelina arborea) - Triyogo, Ananto; Sumardi, Sumardi; Trisyono, Yohanes Andi (Universitas Atma Jaya Yogyakarta, 2010)
Gmelina arborea is one of the important trees for forest plantation. It is used for pulp, paper and plywood. Considering that G. arborea is an exotic type, this species has highly risk of receiving pest and diseases. This research was aimed to study the biological characteristics, attack pattern and distribution of stem borers. Studies were conducted in PT. Sumalindo (East Kalimantan). The sampling plot was 20x20 m2, and the plants were stratified based on the plant age. Observations were directed to determine the species of stem borers and the damage they caused. Xyleutes ceramica and Acalolepta rusticatrix were documented attacking G. arborea, with their damage intensity of 13% and 54.8%. These insect attacked 22% and 64.4% of the plant plantation.